1996
DOI: 10.1046/j.1469-0705.1996.08010037.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial fluid accumulation in asymptomatic postmenopausal women

Abstract: Postmenopausal endometrial fluid accumulation was considered in the past to be related to cancer of the genital organs. Our purpose was to evaluate its prevalence, and its association with cervical stricture, use of hormone replacement therapy and endometrial pathology. A group of 1074 asymptomatic postmenopausal women aged 57-61 (mean 59) years was examined by transvaginal sonography with color Doppler imaging. Women who had an endometrial fluid accumulation underwent endometrial biopsy. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
3
17
0
3
Order By: Relevance
“…The EFC incidence in asymptomatic postmenopausal women is between 4 and 14% [8][9][10][11][12] ; in the present study, the EFC incidence was 4.4%, thereby according with the wider litera ture. We selected our study population from among postmeno pausal women not undergoing hormone replacement therapy; 13 .…”
Section: Discussionsupporting
confidence: 55%
“…The EFC incidence in asymptomatic postmenopausal women is between 4 and 14% [8][9][10][11][12] ; in the present study, the EFC incidence was 4.4%, thereby according with the wider litera ture. We selected our study population from among postmeno pausal women not undergoing hormone replacement therapy; 13 .…”
Section: Discussionsupporting
confidence: 55%
“…Changes in the fluid pH and electrolytes composition of the uterus following menopause are not well understood. There is currently lack of information with regards to the significance of uterine fluid during this period, which may function as lubricant to preserve the normal uterine environment and delaying uterine atrophy [35]. As genistein is widely consumed as a dietary supplement by the post-menopausal women, therefore this effect might be useful to prevent post-menopausal uterine atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fluid in the endometrial cavity of Case No. 21 is of little significance, as the authors themselves have reported in a previous study 3 . In addition, the two other women with uterine cancer also had Stage lb disease and yet had much higher endometrial thickness values.…”
mentioning
confidence: 74%